Global Englishes-Oriented Learning Materials through Disjunctural Pedagogy: Critical Incident Tasks and YouTube-Based Interventions in Indonesian Teacher Education - Imelwaty, Sri; Perpisa, Lili; Ramadhanti, Dina; Husnita, Liza (Research and Innovation in Language Learning, 2025)
The global spread of English challenges teaching traditions that privilege Anglophone norms. Although Global Englishes scholarship stresses the diversity and legitimacy of English beyond native-speaker models, teacher education often treats these issues superficially, producing rhetorical awareness rather than identity change. This study examines how Global Englishes can be enacted through disjunctural pedagogy, a framework that reframes ideological discomfort as a productive space for reflection. Critical Incident Tasks were integrated into four modules using YouTube videos to show communicative breakdowns, unfamiliar accents, and intercultural clashes. Thirty-four pre-service teachers in West Sumatra joined the intervention, which combined guided reflection, peer dialogue, and identity mapping. Data from classroom observations, written reflections, focus groups, and researcher memos were analyzed thematically. Three patterns of engagement emerged. First, resistance, shaped by deficit views of non-standard English. Second, recognition, where intelligibility was seen as relational rather than tied to conformity. Third, identity repositioning, as some participants began to view themselves as legitimate users and future teachers of Global Englishes. These shifts were fragile and uneven. The study concludes that disjunctural pedagogy can foster reflection and identity reorientation but requires systematic embedding, ethical facilitation, and institutional reform for Global Englishes to move beyond rhetorical acceptance.